Embracing Plural Curricula Amid Neoliberalism in Contemporary Universities in Africa: Asante’s Afrocentric Idea Revisited - Phefumula Nyoni; Otilia Chiramba (The Thinker)
This paper focuses on how Asante’s idea of Afrocentricity could assist in the understanding of the main challenges and opportunities associated with curricula in Africa’s post-colonial universities. In terms of methodology, the paper constitutes a conceptual treatise that draws from previous empirical research that focused on Afrocentricity and a plural programme – the extended curriculum programme within a university context where neoliberalism remains dominant. In this regard, the paper combines an extensive review of empirical cases and the authors’ experiences of the extended curriculum programmes in diverse South African universities. Literature was reviewed from a wide range of sources that included Afrocentricity and curriculum transformation through plurality at individual and institutional pedagogic levels. The paper explores the complex nature of pedagogic transformation mainly due to the persistence of Western ideals under a resurgent neoliberal philosophy that shapes practices in contemporary university spaces. The paper thus highlights how Afrocentricity transcends simplistic notions of intellectual discussions as it highlights serious and practical realities that shape the identities, ideals, aspirations, and values of students from disadvantaged backgrounds. In the process, ways in which pedagogic educational aspirations of the students could be redefined through an Afrocentric approach together with constraints are discussed. The individualist-oriented complications posed by neoliberal ideals that tend to contradict and, in some instances, hinder the Afrocentric core principle of inclusivity have left African universities at a crossroads with little to show in terms of progress in the transformation agenda.